Teaching English for Management Students. Does Technology Essential? - Paris, Nirma; K, Ahmad; Samad, Pratiwi (Universitas Sulawesi Barat, 2023)
Independent learning and independent campus (Merdeka Belajar-Kampus Merdeka or MBKM) is a policy of Ministry of Education and Culture (Kemdikbud) which established in early 2020. This program creates challenges for education in Indonesia as teachers and lecturers are required to use technology as a media in teaching. The present study aims to investigate the students’ view toward an application of technology in learning English of management students. The participants of this study were freshman university students majoring in Management, Faculty of Economics, Universitas Sulawesi Barat. A survey questionnaire related the students’ view towards the application of technology in learning English was assigned to the students. Furthermore, an interview was conducted to get depth information. The results of this study showed that the students viewed that using technology in learning English is necessary as it motivated the students in learning English.